Motivational Trajectories of Women Entrepreneurs as Successors to the Family Business - Subadi, Lucky Cahyana; Soenartho, Ferolina; Michelle Thamrin, Jennifer (Universitas Ciputra Surabaya, 2023)
Family enterprises are the most important contributors to Indonesia’s economic resilience. However, the issue of family business succession persists. Female heirs are capable of carrying on the family business. Female entrepreneurs and family business successors in Indonesia and around the world are uncommon. The motivations of female family business heirs will be investigated using self-determination theory. Interview protocols and Interpretative Phenomenological Analysis are used in this qualitative investigation. According to the study, female motivations for developing relationships and self-development exceed women’s autonomy. All three female informants desired cash guarantees as well as repayment to their parents and the family business. Self improvement and family business collaboration are the third motivational trajectory. According to the study, family business players must create possibilities for Indonesian female entrepreneurs’ successors to have careers, build skills, and continue the family business in order for them to feel financially secure and motivated to take over the family firm.